The Effect of Use of Interactive Video Aged 4-5 Years at Ba Aisyiyah Kriwen III Sukoharjo - Setiani, Budi; Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to see whether there is an effect of learning before and after using in-teractive video media on the early reading abilities of children aged 4-5 years at BA Aisyiah Sukoharjo. he purpose of this study is to determine the influence of the role playing learning model on the development of social awareness and skills of lower grade elementary school students. Reading is an activity carried out by looking at reading writing and the process of under-standing the content. Reading will make it easier to understand the meaning, commands, and information or solutions to solving a problem. Interactive video is a learning media that audio-visual elements, such as images, sound, text, graphics and movement, to con-vey information. Seeing these conditions, there is a need for reform by utilizing technol-ogy using interactive video media to improve the ability to pronounce letters, recognize letters fluently, understand how to read and skills in reading writing or images. Methodology: This research design uses a single-group pretest and posttest design. Results: The information analysis method used in this research is simple experimentation and hy-pothesis testing. Hypothesis results were obtained after carrying out the test, before the test (pre-test) and test (post-test), then the researcher analyzed the research results, t count = 8.514 Sig which was accepted. (2-tailed) is 0.001 < 0.05, so Ho is rejected and Ha is accepted, which means that the use of interactive video media has a significant ef-fect on children's beginning reading. Applications/Originality/Value: The sample for this study consisted of 12, namely 5 boys and 7 girls aged 4 -5 years at BA Aisyiyah Sukoharjo.